Design factor identification for product service systems - Moh, Daryl Huizhen (2015)
If we compare the market environment from about 10 years ago as compared to today, there is an obvious change in the way companies are designing their products and also in manufacturing them. In the past the company would pour capital into research and design to create that award-winning product that will bring them fame and fortune. There wasn’t a need for modularity or commonality because the market just wanted that one product. However in the present, the need for customization is something that developed over the past few years of technological improvements show that people want a product with the ability to adapt to their way of life. In this report, we study the factors that lead to product complexity as a whole and compare products from different manufacturers to investigate the commonality.